Oncogenic properties and signaling basis of the PAX8‐GLIS3 fusion gene. Issue 8 (21st May 2020) - Basili, Thais; Dopeso, Higinio; Kim, Sarah H.; Ferrando, Lorenzo; Pareja, Fresia; Da Cruz Paula, Arnaud; da Silva, Edaise M.; Stylianou, Anthe; Maroldi, Ana; Marchiò, Caterina; Rubin, Brian P.; Papotti, Mauro; et al.
Abstract: Hyalinizing trabecular tumors of the thyroid are rare and mostly benign epithelial neoplasms of follicular cell origin, which have recently been shown to be underpinned by the PAX8‐GLIS3 fusion gene. In our study, we sought to investigate the potential oncogenic mechanisms of the PAX8‐GLIS3 fusion gene. Forced expression of PAX8‐GLIS3 was found to increase proliferation, clonogenic potential and migration of human nonmalignant thyroid (Nthy‐ori 3‐1) and embryonic kidney (HEK‐293) cells. Moreover, in xenografts, Nthy‐ori 3‐1 PAX8‐GLIS3 expressing cells generated significantly larger and more proliferative tumors compared to controls. These oncogenic effects were found to be mediated through activation of the Sonic Hedgehog (SHH) pathway. Targeting of smoothened (SMO), a key protein in the SHH pathway, using the small molecule inhibitor Cyclopamine partially reversed the increased proliferation, colony formation and migration in PAX8‐GLIS3 expressing cells. Our data demonstrate that the oncogenic effects of the PAX8 ‐ GLIS3 fusion gene are, at least in part, due to an increased activation of the SHH pathway. Abstract : What's new? In the thyroid, 98% of hyalinizing trabecular tumors (HTTs) express a fusion gene combining PAX8 and GLIS3 . While most of these tumors are benign, the authors of this study found that overexpression of the PAX8‐GLIS3 fusion protein can induce malignant characteristics in thyroid cells. They also found that inhibition of "smoothened" (SMO), a key protein in the Sonic Hedgehog (SHH) pathway, reverses these characteristics. SMO inhibitors may, therefore, offer a potential therapeutic strategy for patients with HTTs that are not amenable to surgical resection.